THE INCIDENT OF VENTILATOR ASSOCIATED PNEUMONIA (VAP) TO PATIENT WITH MECHANICALVENTILATION USING CLINICAL PULMONARY INFECTION SCORE (CPIS) INDICATORS - Dally Rahman; Emil Huriani; Ema Julita (Universitas Airlangga, 2017)
Introduction: Ventilator Associated Pneumonia (VAP) is defined as nosocomial pneumonia that occurs 48 hours after using mechanical ventilation. The incident of VAP in Dr. M. Djamil Padang Hospital was still high when compared to other hospitals that reached only 9%. Nursing intervention that can be used to avoid VAP is endotracheal secretions suctioning. However, the results of the intervention has not been evaluated by using standardized measuring tool. The purpose of this study was to determine the description of signs differences of VAP on first and third day to clients with mechanical ventilation who were performed endotracheal secretions suctioning in ICU Dr. M. Djamil Hospital Padang 2011. Method: The type of this study was a descriptive analytic. The samples were 15 who had a mechanical ventilation during minimal 3 days. Respondents were derived by Accidental Sampling by using Simplified Version of CPIS as a measuring tool. The statistic test is paired t-test. Result: The result of this study showed that there was a significant difference of the signs of VAP on the first and the third day with p=0,048 (< 0.05). Discussion: There were significant difference on symptom of VAP in mechanically ventilated patient in day 1 and day 3. Simplified version of CPIS was sensitive in early determining VAP. Simplified Version of CPIS are expected to be included in standard procedures of patient management and assessment intervention of endotracheal secretions suctioning.